The Use of Matching Game for Teaching Conditional Sentence in Eleventh Graders of SMK Takhassus Al-Qur’an Wonosobo - Arini, Khusna; Widyantoro, Arif (Metaphor, 2025)
The aim of this research was to know whether Matching Game gives the impact or not in teaching conditional sentence at SMK Takhassus Al-Qur’an Wonosobo. The method used was classroom action research (CAR) by using qualitative and quantitative approach. The researcher used pre-cycle, cycle I and cycle II to find the data. T-test was used to analyze it. Having analyzed the data, the researcher revealed that the student’s understanding in cycle II was higher than pre-cycle and cycle I. There was positive impact in teaching conditional sentence using Matching Game at SMK Takhassus Al-Qur’an Wonosobo. The T-test result was 10.8 and T-table in degree of freedom 33 at the significant 0.05 was 2.034. The hypothesis was accepted because T-test was higher than T-table. It means that Matching Game is effective for teaching conditional sentence.